1973
DOI: 10.1055/s-0028-1096728
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin and Glucose Uptake by lsolated Rat Diaphragm

Abstract: 145Recently, an impairment of glucose assimilation and insulin output produced by calcitonin has been demonstrated in men (Zieg/er, Bel/winkel, Schmidtchen and Minne 1972). A possible competitive action of calcitonin to insulin was studied by means of isolated diaphragm museie method (Gemil/ 1941, Vallanc~Owen 1954. The diaphragms were excised from male rats weighing 100 gm and incubated in 2 ml KrebsHenseleit buffer under a gas phase (95% oxygen -5% carbon dioxide) for 90 minutes with an initial glucose con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1980
1980
1981
1981

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…CT inhibits glucose uptake stimulated by insulin in diaphragm muscle of rats, and that the effect of CT is not mediated by hypocalcemia (Gozarin andFlorescu, 1973 and1974). On the other hand, we have found that CT increases glucose concentration in the serum of fed and fasted rats (Yamaguchi and Yamamoto, 1977).…”
mentioning
confidence: 99%
“…CT inhibits glucose uptake stimulated by insulin in diaphragm muscle of rats, and that the effect of CT is not mediated by hypocalcemia (Gozarin andFlorescu, 1973 and1974). On the other hand, we have found that CT increases glucose concentration in the serum of fed and fasted rats (Yamaguchi and Yamamoto, 1977).…”
mentioning
confidence: 99%